Molecular dissection of amyloid disaggregation by human HSP70 - Wentink, Anne; Nillegoda, Nadinath B.; Feufel, Jennifer; Ubartaitė, Gabrielė; Schneider, Carolyn P.; De Los Rios, Paolo; Hennig, Janosch; Barducci, Alessandro; Bukau, Bernd (Nature, 2020)
The deposition of highly ordered fibrillar-type aggregates into inclusion bodies is a hallmark of neurodegenerative diseases such as Parkinson’s disease. The high stability of such amyloid fibril aggregates makes them challenging substrates for the cellular protein quality-control machinery1,2. However, the human HSP70 chaperone and its co-chaperones DNAJB1 and HSP110 can dissolve preformed fibrils of the Parkinson’s disease-linked presynaptic protein α-synuclein in vitro3,4. The underlying mechanisms of this unique activity remain poorly understood. Here we use biochemical tools and nuclear magnetic resonance spectroscopy to determine the crucial steps of the disaggregation process of amyloid fibrils. We find that DNAJB1 specifically recognizes the oligomeric form of α-synuclein via multivalent interactions, and selectively targets HSP70 to fibrils. HSP70 and DNAJB1 interact with the fibril through exposed, flexible amino and carboxy termini of α-synuclein rather than the amyloid core itself. The synergistic action of DNAJB1 and HSP110 strongly accelerates disaggregation by facilitating the loading of several HSP70 molecules in a densely packed arrangement at the fibril surface, which is ideal for the generation of ‘entropic pulling’ forces. The cooperation of DNAJB1 and HSP110 in amyloid disaggregation goes beyond the classical substrate targeting and recycling functions that are attributed to these HSP70 co-chaperones and constitutes an active and essential contribution to the remodelling of the amyloid substrate. These mechanistic insights into the essential prerequisites for amyloid disaggregation may provide a basis for new therapeutic interventions in neurodegeneration.